Epidemiology, clinical ramifications, and cellular pathogenesis of COVID-19 mRNA-vaccination-induced adverse cardiovascular outcomes: A state-of-the-heart review - Almas, Talal; Rehman, Sarah; Mansour, Eyad; Khedro, Tarek; Alansari, Ali; Jahanzeb, Malik *; Alshareef, Norah; Nagarajan, Vikneswaran Raj; Al-Awaid, Abdulla Hussain; Alsufyani, Reema; Alsufyani, Majid; Rifai, Ali; et al. (Elsevier, 2022)
The coronavirus disease 2019 (COVID-19) has overwhelming healthcare systems globally. To date, a myriad of therapeutic regimens has been employed in an attempt to curb the ramifications of a severe COVID-19 infection. Amidst the ongoing pandemic, the advent and efficacious uptake of COVID-19 vaccination has significantly reduced disease-related hospitalizations and mortality. Nevertheless, many side-effects are being reported after COVID-19 vaccinations and myocarditis is the most commonly reported sequelae post vaccination. Majority of these diseases are associated with COVID-19 mRNA vaccines. Various studies have established a temporal relationship between these complications, yet the causality and the underlying pathogenesis remain hypothetical. In this review, we aim to critically appraise the available literature regarding the cardiovascular side effects of the various mRNA vaccines and the associated pathophysiology.